A novel D90_K91insN mutation in exon 4 of the SOD1 gene caused familial amyotrophic lateral sclerosis in a Chinese pedigree. Issue 7 (2nd October 2018) - Li, Yanran; Sun, Bo; Chen, Siyu; Ren, Yuting; Cui, Fang; Yang, Fei; Chen, Zhaohui; Ling, Li; Huang, Xusheng
Abstract: We reported a novel heterozygous duplication mutation (c.272_274dupACA, D90_K91insN) in exon 4 of the SOD1 gene in a Chinese pedigree. This pedigree demonstrates an autosomal dominant pattern of inheritance, with potentially reduced penetrance. The clinical phenotype was rather uniform with a distal lower extremity onset, predominant involvement of lower motor neurons (LMNs), and a relatively short survival time (mean 2.6 years) compared with other mutations in the loop V structure of SOD1. We also detected that the average SOD1 activity in D90_K91insN mutation carriers is 68.5% of wild-type controls. In conclusion, we identified the first non-frameshift duplication mutation in loop V of the human SOD1 in the Chinese population, suggesting the importance of the loop V structure in the pathogenicity of FALS.